Nigeria's Niger Delta : Militancy, Amnesty, And The Post-Amnesty Environment - Abidde, Sabella Ogbobode, 1962- (African governance and development., 2017)
The problems and challenges of the Niger Delta predate Nigeria as a Republic. The resultant violence can be traced to 1966, when the late Isaac Boro and his colleagues attempted to secede from Nigeria due, in large part, to the underdevelopment of the region. Historical reality aside, since 1970 oil has displaced agriculture as Nigeria's primary revenue earner and it has, for the last four decades, been the nation's breadbasket. But in spite of this, the Niger Delta remains vastly underdeveloped and has been given the least federal presence. These deficiencies led to high unemployment, social dislocations, youth restiveness, and extralegalities. It was these realities that bred disaffection with the government and the multinational oil companies and eventually, to violent militancy. Between 2003 and 2009, it also led to low intensity conflict between militant youths and the Nigerian government. In the summer of 2009, however, the Nigerian government extended an offer of presidential pardon (amnesty) to the militants. The amnesty program was intended to bring peace and quiet to the region. However, this has not been the case. In spite of the financial and political resources that have been expended, the region continues on the path of volatility. This book looks at the issue of nationhood, the cause and cost of the crisis, past approaches and current efforts at solving the crisis. In addition, it offers a tenable solution to the decades-old crisis. Furthermore, the case is made that unless there is a fundamental restructuring of the Nigerian state and its governing structure and institutions, the problems of the region and the larger problems that makes the country such a difficult to place to live in and govern, is likely to continue. --